Altered lipid levels in untreated patients with early polymyositis. - Han Wang; Yingying Cai; Lin Cai; Yingchun Hu; Xianxiang Chen; Juelin Deng (PLoS ONE)
Background Little is known so far on the lipid profile in polymyositis (PM) patients. Our aim is to identify lipid profiles in untreated patients with early PM, to assess the association between lipid profiles and C-reactive protein (a sensitive marker of inflammation) in these patients. Methods and findings This work was conducted as a case-control study. Sixty untreated patients with PM and 60 age- and sex-matched healthy controls were included. The duration of PM was less than six months, and none of them had received intermittent or regular corticosteroids or disease-modifying antirheumatic drugs or biological agents prior to the study. Triglyceride (TG), total cholesterol (TC), LDL-cholesterol (LDL-C), and HDL-cholesterol (HDL-C), and C-reactive protein (CRP) were assessed using standard techniques. Thirty patients (50%) had a decreased level of HDL-C and 47% had an increased level of TG. The levels of HDL-C, LDL-C, and TC in PM were significantly lower than in controls (P<0.001, P<0.01, P<0.001, respectively). The level of TG was significantly higher in PM than in controls (P<0.001). The level of very low LDL-cholesterol (VLDL-C), and the ratios of VLDL-C/LDL-C, TC/HDL-C, and LDL-C/HDL-C were significantly higher than in controls (all P<0.001). Serum CRP levels correlated negatively with HDL-C (r = -0.352, P = 0.006) and TC (r = -0.262, P = 0.043). After adjustment for age, gender, smoking, drinking, body mass index, and pulmonary fibrosis/infection, linear regression model demonstrated that CRP is associated with HDL-C among PM patients (P = 0.028). Conclusions Dyslipidemia is a common feature in patients with PM that is characterized by a decrease in HDL-C and an increase in TG, suggesting a high risk of atherosclerosis. The Inflammatory condition in PM may account for the metabolism of HDL-C.